(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
The purpose of the following scientific research is to highlight the analysis and comparison of the intellectual revolution brought by Agatha Christie to the world of detective writing on the example of the work of three writers who are considered bright representatives of their time: Edgar A. Poe. In addition, this is the positive impact of the revolution on students and society in general. The purpose of this article is not to claim that Edgar Poe’s methods are outdated or useless. The objects of the article are the works "The Murder of Roger Ackroyd" from the series by Agatha Christie Hercule Poirot, "Murder on the Street of Morg" by Edgar A. Poe. The puzzle-solving methods of the three-detective works mentioned above are compared with each other. The expected result of the article is the influence of writing methods in the detective genre, which have evolved over time, on today’s works.